Ultrasound-Guided Percutaneous Transthoracic Biopsy by Pulmonologists - Verma, Avatar; Bhatta, Narendra; Shahi, Rejina; Lama, Urmila; Aryal, Prakash; Pantha, Srijan; Hamal, Sangita; Mishra, Deebya Raj (Nepalese Respiratory Journal, 2024)
Background: Ultrasound-guided transthoracic needle biopsy (USG-TTNB) is a simple and safe procedure carried out to obtain a tissue sample for confirmation of the diagnosis of various thoracic pathologies. These procedures are usually carried out by radiologists in our country. However, there is good efficacy and fewer complications even in the hands of chest physicians, as shown by many studies published abroad. Considering this, the study is carried out to evaluate outcomes of USG-TTNB by pulmonologists in Nepal. Objective: To study the efficacy and complications associated with USG-guided transthoracic needle biopsies performed by pulmonologists. Methods: Retrospective analysis of 77 patients undergoing USG-TTNB by pulmonologists at BPKIHS from November 2019 to November 2023 were analyzed. The efficacy of the procedure and the complication rate were derived. Efficacy was calculated as proportion of the patients who had undergone the biopsy and resulted in a clinically contributory specimen. Results: Mean age: 62.5 ± 13.7 years; 63.6% female. Transthoracic Fine Needle Aspiration showed a diagnostic yield of 82.6 % of patients, whereas that of trucut biopsy was 86.7 % with a combined diagnostic yield of 94 %. Pneumothorax occurred in four (5.2 %) of patients, and hemothorax occurred in two (2.6 %) of patients. Conclusion: USG-guided percutaneous transthoracic biopsy by a pulmonologist is a procedure with good diagnostic yield and a lower complication rate.